Cell division cycle protein 42-driven activation of the MKK3/6-p38 signaling pathway participates in cardiac remodeling in mice - Wen, Ke; Xie, Lin; Liu, Quan-Wen; Yu, Guan-Hui; Qiao, Xu-Hui; Huang, Yu-Chun; Wang, Lu; Li, Xin; Wen, Li-Dan; Wang, Xiao-Lei; He, Jing; Xiao, Xin-Yu; et al. (Cellular and molecular life sciences : CMLS, 2025)
Cell division cycle protein 42 (Cdc42) is a member of the Rho GTPase subfamily that serves as a signal mediating factor in cell cycle division, cytoskeleton arrangement, cell polarization, membrane trafficking and signal transduction. However, the role of Cdc42 in cardiac remodeling, including hypertrophy and fibrosis, remains controversial. This study aimed to clarify the role and underlying mechanism of Cdc42 in cardiac remodeling. Cardiac Cdc42 knockout (Cdc42 CKO ) mice were generated by crossing Cdc42 loxP/loxP mice with MLC2v-Cre mice. Mouse cardiac remodeling models were induced by subcutaneous administration of AngII (1500 ng/kg/min) for 7 days or transverse aortic constriction (TAC) for 2 or 8 weeks. Our results showed that cardiac Cdc42 deletion significantly suppressed AngII- or TAC-induced cardiac hypertrophy and fibrosis and improved cardiac function in mice. Cdc42 CKO or specific inhibition of Cdc42, markedly inhibited Ang II-mediated activation of the MKK3/6-p38 cascade in the heart and in isolated newborn/adult mouse cardiomyocytes or H9c2 cells. Furthermore, Cdc42 overexpression increased the surface area and hypertrophic gene expression in myocytes, whereas ML141 (a Cdc42 inhibitor) and SB203580 (a p38 inhibitor) specifically decreased p38 activation and hypertrophy in Cdc42-overexpressing or AngII-induced hypertrophic cardiomyocytes, indicating that p38 is a downstream effector of Cdc42 in cardiac hypertrophy. Taken together, our results demonstrated that Cdc42 is a key driver of cardiac remodeling via activation of the p38 signaling pathway. Graphical abstract Highlights Cell division cycle protein 42 (Cdc42) participates in cell cycle division, cytoskeleton arrangement, cell polarization, membrane trafficking and signal transduction. Cardiac deletion of Cdc42 protects against multiple mouse models of cardiac remodeling, including hypertrophy and fibrosis, both in vivo and in vitro . Cardiac Cdc42 deficiency attenuates cardiac remodeling by suppressing hypertrophy, apoptosis and inflammation via inhibiting MKK3/6-p38 signaling pathway in myocardium.